Unraveling the Guest-Induced Switchability in the Metal-Organic Framework DUT-13(Zn)** - Felsner, Bodo; Bon, Volodymyr; Evans, Jack D.; Schwotzer, Friedrich; Grunker, Ronny; Senkovska, Irena; Kaskel, Stefan (Chemistry - A European Journal, 2021)
The switching mechanism of the flexible framework Zn4O(benztb)1.5 (benztb=N,N,N’,N’-benzidine tetrabenzoate), also known as DUT-13, was studied by advanced powder X-ray diffraction (PXRD) and gas physisorption techniques. In situ synchrotron PXRD experiments upon physisorption of nitrogen (77 K) and n-butane (273 K) shed light on the hitherto unnoticed guest-induced breathing in the MOF. The mechanism of contraction is based on the conformationally labile benztb ligand and accompanied by a reduction in specific pore volume from 2.03 cm3 g−1 in the open-pore phase to 0.91 cm3 g−1 in the contracted-pore phase. The high temperature limit for adsorption-induced contraction of 170 K, determined by systematic temperature variation of methane adsorption isotherms, indicates that the DUT-13 framework is softer than other mesoporous MOFs like DUT-49 and does not support the formation of overloaded metastable states required for negative gas-adsorption transitions.
CRIS-Team Scopus Importer:2022-04-14
Keywords: breathing metal-organic frameworks; DUT-13; flexibility; in situ powder X-ray diffraction